2020
DOI: 10.1097/pec.0000000000002122
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the BIG Score in Predicting Mortality in Normotensive Children With Trauma

Abstract: Objectives: Children have a larger reserve for traumatic hemorrhagic shock, requiring a score that uses physiologic variables other than hypotension. Recently, the BIG score comprising admission base deficit, international normalized ratio, and the Glasgow Coma Scale has been reported to predict traumatic mortality. We aimed to validate the performance of the BIG score in mortality prediction of normotensive children with trauma. Methods:We reviewed 1046 injured children (<18 years) who visited a Korean academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…GCS is a strong predictor of mortality. The recent Korean and U.S. studies have shown the AUCs of GCS for mortality ranging from 0.90 to 0.95 7,12) . In addition, according to the former study, the AUC of GCS approached that of BIG score (GCS, 0.90 vs. BIG score, 0.94) 7) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…GCS is a strong predictor of mortality. The recent Korean and U.S. studies have shown the AUCs of GCS for mortality ranging from 0.90 to 0.95 7,12) . In addition, according to the former study, the AUC of GCS approached that of BIG score (GCS, 0.90 vs. BIG score, 0.94) 7) .…”
Section: Discussionmentioning
confidence: 99%
“…The recent Korean and U.S. studies have shown the AUCs of GCS for mortality ranging from 0.90 to 0.95 7,12) . In addition, according to the former study, the AUC of GCS approached that of BIG score (GCS, 0.90 vs. BIG score, 0.94) 7) . The younger median age of the non-survivors in our study corresponds with the previously reported values (survivors, 9.0-9.3 vs. nonsurvivors, 7.0-7.2 years) 13,14) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations